Advances in Characterization of Human Sirtuin Isoforms: Chemistries, Targets and Therapeutic Applications - Cen, Y.; Y. Youn, D.; A. Sauve, A. (Current Medicinal Chemistry, 2011)
Since the discovery in 2000 that the yeast sirtuin called “Sir2” catalyzes NAD+ dependent histone deacetylation, a wave of research has focused on evaluating the biochemical and biological functions of sirtuins. Sirtuins are activated by low calorie diets in numerous organisms and are found throughout biology in species from archaea to humans. There are seven human sirtuin isoforms called SIRT1-SIRT7. The biochemical functions of SIRT1, SIRT2, SIRT3, SIRT5 and SIRT6 have been reported and NAD+ dependent deacetylase activities confirmed. In some instances the biological target substrates for each isoform have been identified, helping to connect distinct biological processes to sirtuin regulation. This knowledge has informed potential drug design strategies that target distinct sirtuin isoforms. This review presents current knowledge of biochemical activities of SIRT1-7 in humans and the biological consequences of these sirtuin activities. Regulatory principles that govern sirtuin deacetylation activity in cells are discussed as well as strategies for how sirtuins can be targeted by small molecules. Finally, this review updates research on pharmacologic sirtuin activation and allostery on sirtuins and considers new developments for detection and isolation of sirtuins in complex mixtures.
Keywords: nicotinamide